Using the Statistical Concept of "Severity" to Assess Seemingly Contradictory Statistical Evidence (with a Particular Application to Damage Estimation) - Peter Bon̈isch; Roman Inderst (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2020)
When parties present divergent econometric evidence, the court may view such evidence as contradictory and thus ignore it completely, without conducting closer analysis. We develop a simple method for distinguishing between actual and merely apparent contradiction based on the statistical concept of the "severity" of the furnished evidence. Again using "severity", we also propose a method for reconciling divergent findings in instances of mere seeming contradiction. Our chosen application is that of damage estimation in follow-on cases.
urn:nbn:de:hebis:30:3-616436
Keywords: 330; Cartel damages; severity; statistical testing